2017
DOI: 10.4238/gmr16039724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of eight methods to isolate genomic DNA from Hancornia speciosa

Abstract: ABSTRACT. Mangabeira (Hancornia speciosa) is a native fruit tree found mainly in the Cerrado biome and shows great economic potential due to its multiple uses; the fruits are used in agriculture, are important as a food resource, and can be consumed in natura or processed. Due to a reduction in the area of ecosystems where it occurs, mangabeira is threatened by genetic erosion in Brazil. The characterization of the genetic diversity of plants can provide the basis for strategies to protect and conserve endange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Moreover, DNA extraction by kits has a higher cost, and a few studies in the literature have reported that DNA extraction using a commercial kit generated so little DNA that molecular studies were not possible (Bitencourt et al 2007). Thus, it is important to modify and adapt the protocols described in the literature and adjust the concentrations of reagents to adapt to the existing variation in the chemical composition of plant tissues (Viana et al 2015;Almeida et al 2017).…”
Section: A Simple and Cost-effective Methods For Dna Extraction Suitable For Pcr In "Sucupira Branca"mentioning
confidence: 99%
“…Moreover, DNA extraction by kits has a higher cost, and a few studies in the literature have reported that DNA extraction using a commercial kit generated so little DNA that molecular studies were not possible (Bitencourt et al 2007). Thus, it is important to modify and adapt the protocols described in the literature and adjust the concentrations of reagents to adapt to the existing variation in the chemical composition of plant tissues (Viana et al 2015;Almeida et al 2017).…”
Section: A Simple and Cost-effective Methods For Dna Extraction Suitable For Pcr In "Sucupira Branca"mentioning
confidence: 99%
“…However, in the utilization of conventional protocols of extraction, there is the possibility of optimization to minimize the complex formation of DNA with these compounds, besides being a more economical method when compared to commercial kits (Raimundo et al 2018). Thus, there are a great diversity of protocols for the extraction of genomic DNA that were efficient for vegetable species (Viana et al 2015;Almeida et al 2017;Furtado Filho et al 2021;Silva et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Em linhas gerais, o objetivo de qualquer protocolo de extração consiste na obtenção de um DNA de alta qualidade e com boa concentração, Brazilian Journal of Development, Curitiba, v.7, n.4, p. 35765-35779 apr 2021 de forma rápida, pouco onerosa e eficiente. Dessa forma, estudos básicos sobre métodos de extração de DNA de alta qualidade são cruciais para o desenvolvimento de técnicas moleculares (ALMEIDA et al, 2017;LIMA et al, 2020;SOUSA et al, 2014;VIANA et al, 2015). Esses estudos podem resultar em novas metodologias visando aperfeiçoar a extração do DNA de uma determinada espécie (WALDSCHMIDT, 1997).…”
Section: Introductionunclassified